Selective therapeutic hypothermia: A review of invasive and noninvasive techniques - David Straus; Vinay Prasad; Lorenzo Munoz (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: Therapeutic hypothermia is a promising treatment to prevent secondary neurologic injury. Clinical utility is limited by systemic complications of global hypothermia. Selective brain cooling remains a largely uninvestigated application. We review techniques of inducing selective brain cooling. METHOD: Literature review. RESULTS: Strategies of inducing selective brain cooling were divided between non-invasive and invasive techniques. Non-invasive techniques were surface cooling and cooling via the upper airway. Invasive cooling methods include transvascular and compartmental (epidural, subdural, subarachnoid and intraventricular) cooling methods to remove heat from the brain. CONCLUSION: Selective brain cooling may offer the best strategy for achieving hypothermic neuroprotection. Non-invasive strategies have proven disappointing in human trials. There is a paucity of human experiments using invasive methods of selective brain cooling. Further application of invasive cooling strategies is needed.